EPIDEMIOLOGY OF CHRONIC OBSTRUCTIVE PULMONARY DISEASE (COPD) IN INDONESIA: A LITERATURE REVIEW - Saragi, Dhea Rizky Fitri; Susanti, Nofi; Nabilah, Nanda; Efri, Puti Miratil Hayati; Andriani, Riski (HEARTY, 2024)
In Indonesia, Chronic Obstructive Pulmonary Disease (COPD) is a non-communicable disease that poses a public health problem. Its main risk factors include active and passive smoking, air pollution, as well as genetic factors. The prevalence of COPD is likely to increase due to high smoking rates among the Indonesian population and high levels of air pollution in some areas. This study aims to describe the problem of COPD in Indonesia epidemiologically from the definition, diagnosis, symptoms, terminology, prevention, treatment, pathogenesis, prevalence in Indonesia and complications of COPD. The research method used is qualitative and the primary literature of this research comes from books, articles, journals, and seminar papers. Descriptive analysis was then used to process the data that had been obtained. Based on the results of research (WHO) said that in 2002, around 64 million people were affected by COPD and 3 million people died from the disease. In 2020, it is estimated that (COPD) will be the third highest cause of death in the world. The conclusion of this study is that it is important to take preventive measures such as maintaining hand hygiene, avoiding exposure to air or cigarette smoke, and getting vaccinations as recommended by the doctor to reduce the risk of infections that can worsen the condition of COPD. Lack of awareness of the importance of COPD prevention and management is also a challenge that needs to be addressed.